What can general practice learn from complementary medicine? - White, P (2000)
Complementary medicine is popular in Britain. This suggests that patients who use complementary medicine believe that there are deficiencies in the care they receive from their general practitioners (GPs). Studies of patients using complementary medicine have shown that these patients are sometimes dissatisfied with the communication skills of conventional doctors, the explanations they give for their illnesses, the dangers of modern drugs, and a perceived lack of holistic care. The patients using complementary medicine trusted their bodies' own healing potential and they generally believed that they had more control over their bodies than those patients who did not use complementary medicine. They particularly valued the longer appointment times usually given by the complementary therapists and also the in-depth discussions of their illnesses. Patients using complementary medicine tended to be those with chronic illnesses and these patients particularly valued the positive approach of, and the psychological support given by, the complementary therapists. General practitioners know that all of these aspects of care are important, but the fact that many of our patients go to complementary therapists to satisfy them should encourage us to look at our own practices to see how we as GPs can fulfill these needs.